Unveiling immune resistance mechanisms in nasopharyngeal carcinoma and emerging targets for antitumor immune response: tertiary lymphoid structures - Huilin Wang; Yuting Zhan; Jiadi Luo; Weiyuan Wang; Songqing Fan (Journal of Translational Medicine)
Abstract Nasopharyngeal carcinoma (NPC) is a prevalent malignancy in China, commonly associated with undifferentiated cell types and Epstein-Barr virus (EBV) infection. The presence of intense lymphocytic infiltration and elevated expression of programmed cell death ligand 1(PD-L1) in NPC highlights its potential for immunotherapy, yet current treatment outcomes remain suboptimal. In this review, we explore the tumor microenvironment of NPC to better understand the mechanisms of resistance to immunotherapy, evaluate current therapeutic strategies, and pinpoint emerging targets, such as tertiary lymphoid structures (TLSs), that could enhance treatment outcomes and prognostic accuracy. TLSs have demonstrated positive prognostic value in NPC, making them a promising target for future therapies. This review summarizes the key characteristics of TLSs and latest research in the context of NPC. We are optimistic that targeting TLSs could improve immunotherapy outcomes for NPC patients, ultimately leading to more effective treatment strategies and better patient survival.